Progressive Worsening of Snoring as a Rare Presentation of HPV-Positive Oropharyngeal Squamous Cell Carcinoma - V Sha Kri Eh Dam; Azliana Aziz; Sarah Zulkarnain; Nur Asyilla Che Jalil; Irfan Mohamad (Acta Medica, 2022)
The incidence of oropharyngeal squamous cell carcinoma (OPSCC) especially human papillomavirus (HPV) associated type is increasing in trend despite reducing in other head and neck squamous cell carcinoma. Muffled voice, dysphagia, neck mass and pain over the throat are among the common presentations; however, health care professional should be aware of unusual presentation to avoid delay in management. We present a case of HPV-positive OPSCC with a rare presentation; progressive worsening of snoring for 6 months duration. Patient sougth medical attention at the some of private clinics for the past 2 months, however, was told to have a normal tonsillar enlargement. Subsequently, patient was referred to our center with impression of obstructive sleep apnea. We highlight the important of early referral to appropriate center and otorhinolaryngology for assessment in cases presented with worsening snoring.